Predicting Marital Satisfaction Based on Gender Beliefs and Thinking Styles of Married Women in Tehran - Firuzeh Keyhan; Susan Saber (Salāmat-i ijtimā̒ī, 2016)
Background and Objective: The role of gender beliefs and thinking styles in creating an interpersonal understanding are significant and it can be said that if the family environment, education, and employment of people with their thinking style is consistent or inconsistent, it can have stronger or weaker effect at different stages of life. The aim of this study was to predict marital satisfaction based on gender beliefs and thinking styles of married women in Tehran. Materials and Methods: The method of study was correlation. The study population consisted of all married women referred to health centers of area two of Tehran in 2015-16. Using cluster sampling, 220 samples were selected. Pearson correlation coefficient and multiple regression analysis were used. Results: The results showed that marital satisfaction has a significant positive correlation with the belief masculine gender (P<0.01), respectively. Marital satisfaction was significantly and the beliefs of female sexuality and gender. Also liberal thinking style (two-tailed test, P<0.01) and conservative (P<0.05) has had a significant positive correlation with marital satisfaction. Legislator thinking style, executive, judicial thinking style, holistic and component-oriented. There is no significant relationship with marital satisfaction. Thinking styles and gender beliefs have relation with marital satisfaction. Conclusion: The results of this study showed that gender beliefs and thinking styles is an important resource to predict marital satisfaction.